Synthesis of substituted pyridines and pyridazines via ring closing metathesis. - Donohoe, T; Fishlock, L; Basutto, J; Bower, J; Procopiou, P; Thompson, A (2009)
RCM can be used to make aromatic heterocycles, namely pyridines and, for the first time, pyridazines; the key step after RCM involves elimination of sulfinate to provide the aromatic system.